2018
DOI: 10.1136/jech-2018-211203
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing violence in early secondary school predicts subsequent student impairment

Abstract: Almost all students witnessed school violence, which predicted impairment. Witnessing violence was associated with risk of subsequent adjustment problems 2 years later. Directly experienced victimisation showed a comparable magnitude of risk. This suggests that when it comes to symptoms of conduct disorder, witnessing violence might have the same impact as experiencing it directly. Witnessing earlier covert and major violence predicted social impairment whereas minor violence predicted psychological and academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Children who experience being bullied at primary school age are more likely to be bullied as a teenager and both increase the risk of victimization as an adult. [5] Those subjected to bullying at any age are more likely to experience a range of poorer health and social outcomes subsequently[1,2,4,6] including lower self-esteem,[7] poorer mental health,[8] poorer physical health,[9] poorer quality adult relationships[7] and lower educational attainment. [10] In addition, they are also more likely to exhibit anti-social behaviours in later life including committing crimes[9,10] and are at increased risk of attempting and completing suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Children who experience being bullied at primary school age are more likely to be bullied as a teenager and both increase the risk of victimization as an adult. [5] Those subjected to bullying at any age are more likely to experience a range of poorer health and social outcomes subsequently[1,2,4,6] including lower self-esteem,[7] poorer mental health,[8] poorer physical health,[9] poorer quality adult relationships[7] and lower educational attainment. [10] In addition, they are also more likely to exhibit anti-social behaviours in later life including committing crimes[9,10] and are at increased risk of attempting and completing suicide.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, moderate and severe perceived difficulties were independently associated with feeling unsafe in both sexes. Longitudinal studies have shown that both witnessing violence and victimization at school predicted later internalizing and externalizing problems ( 33 , 34 ). Individuals with mental health difficulties may start feeling unsafe because they perceive a lack of social support or stigma ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physical aggression includes hitting, pinching, pulling hair, or throwing things at someone else ( Solberg & Olweus, 2003 ). Verbal aggression includes name-calling, swearing, saying mean things, or making fun of a peer ( Janosz et al, 2018 ). Relational aggression uses the relationship to harm, for instance, by undermining a peer’s reputation.…”
Section: Student Involvement In Peer Aggressionmentioning
confidence: 99%
“…Finally, student exposure to school violence (verbal and physical) as witnesses can also be impacted by their involvement in peer aggression and impede their feeling of safety at school ( Janosz et al, 2018 ). Students involved in aggression are more likely to report witnessing school violence ( Goldweber et al, 2013b ; Nylund et al, 2007 ; O’Brennan et al, 2009 ).…”
Section: Concurrent Validity: School Belonging Depressive Thoughts An...mentioning
confidence: 99%
See 1 more Smart Citation